2008
DOI: 10.1074/jbc.m709777200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermodynamic Analyses of Solute-binding Protein from Bifidobacterium longum Specific for Core 1 Disaccharide and Lacto-N-biose I

Abstract: Recently, a gene cluster involving a phosphorylase specific for lacto-N-biose I (LNB; Gal␤1-3GlcNAc) and galacto-N-biose (GNB; Gal␤1-3GalNAc) has been found in Bifidobacterium longum. We showed that the solute-binding protein of a putative ATP-binding cassette-type transporter encoded in the cluster crystallizes only in the presence of LNB or GNB, and therefore we named it GNB/LNB-binding protein (GL-BP). Isothermal titration calorimetry measurements revealed that GL-BP specifically binds LNB and GNB with K d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 72 publications
5
97
0
2
Order By: Relevance
“…Kitaoka et al (19,20) proposed a metabolic pathway for GNB from core-1 mucin-type O-glycans and Gal-␤1,3-GlcNAc (LNB) from human milk oligosaccharides based on the characterization of the genes encoded in the GNB/LNB operon (BLLJ_1620-BLLJ_1626) of B. longum. Fushinobu et al (21,22) characterized the GNB/LNB-binding protein (BLLJ_1626) of an ATP-binding cassette (ABC)-type sugar transport system in the GNB/LNB pathway. As shown in supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Kitaoka et al (19,20) proposed a metabolic pathway for GNB from core-1 mucin-type O-glycans and Gal-␤1,3-GlcNAc (LNB) from human milk oligosaccharides based on the characterization of the genes encoded in the GNB/LNB operon (BLLJ_1620-BLLJ_1626) of B. longum. Fushinobu et al (21,22) characterized the GNB/LNB-binding protein (BLLJ_1626) of an ATP-binding cassette (ABC)-type sugar transport system in the GNB/LNB pathway. As shown in supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…79) Afterwards, our structural and thermodynamic analyses revealed the detailed molecular mechanism of its disaccharide binding. 80) Isothermal titration calorimetry measurements indicated that GL-BP strongly binds GNB (K a ¼ 9:7 Â 10 7 M À1 ) and LNB (K a ¼ 1:2 Â 10 7 M À1 ), but does not bind LacNAc, lactose, galactose, GlcNAc, or GalNAc. The affinity for a major HMO tetrasaccharide, LNT, was 1,000-fold weaker than that for GNB (K a ¼ 9:1 Â 10 4 M À1 ).…”
Section: Sugar Transport Systemmentioning
confidence: 99%
“…We have determined that bifidobacteria possess a gene cluster encoding the unique metabolic pathway for lacto-N-biose I (Gal1-3GlcNAc), in which the disaccharide is transported to the cytoplasm through a specific ABC-type transporter, 12,13) phosphorolyzed by galacto-N-biose (Gal1-3GalNAc)/lacto-N-biose I phosphorylase (renamed from lacto-N-biose phosphorylase after the discovery of the lacto-N-biose I specific enzyme), [14][15][16] and finally metabolized in the glycolytic and aminosugar metabolic pathways. 17) Although lacto-N-biose I is not present in free disaccharide form in human milk, it occurs as a building unit of type I oligosaccharides, containing lacto-N-tetraose (Gal1-3GlcNAc1-3Gal1-4Glc) as the core structure.…”
mentioning
confidence: 99%